Tanggung Jawab Hukum PPAT atas Dana BPHTB yang Tidak Disetorkan ke Kas Negara: Suatu Kajian Yuridis - Ayulina, Jennitri; Ismed, Mohamad; Sri Marniati, Felicitas (Prodi Tata Negara (Siyasah) IAIN Langsa, 2025)
This study examines the legal consequences and responsibilities of Land Deed Officials (PPAT) regarding entrusted Land and Building Rights Acquisition Fee (BPHTB) payments that are not deposited into the state treasury. Article 25 paragraph (2) of the Regulation of the Minister of ATR/BPN No. 3 of 2023 requires proof of BPHTB payment in every transfer of land or building rights. However, in practice, clients often entrust BPHTB payments to PPAT, and some officials fail to forward the funds, creating legal problems. Using a normative juridical method with statutory, conceptual, analytical, and case approaches, this research analyzes legal materials from primary, secondary, and tertiary sources. The results show that PPAT who fails to deposit entrusted BPHTB funds may face criminal sanctions under Articles 372–376 of the Criminal Code, particularly Article 374 on embezzlement, since Government Regulation No. 24 of 2016 does not explicitly regulate such sanctions. The implication is the need for strict legal accountability of PPAT to ensure legal certainty, protect the public, and safeguard state revenue.